2019
DOI: 10.33594/000000055
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma and Nuclear Paraspeckles: Induction in Chemoresistance and Prediction for Poor Survival

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 49 publications
(60 reference statements)
2
6
0
Order By: Relevance
“…Cawthorn et al reported that up-regulated HSP90B1 is related with distant metastasis [37]. Kessler et al reported that Paraspeckle Component 1 (PSPC1) is significantly related with poor prognosis in hepatocellular carcinoma [38]. The results in current study further supported the credibility of these findings above in previous researches.…”
Section: Discussionsupporting
confidence: 86%
“…Cawthorn et al reported that up-regulated HSP90B1 is related with distant metastasis [37]. Kessler et al reported that Paraspeckle Component 1 (PSPC1) is significantly related with poor prognosis in hepatocellular carcinoma [38]. The results in current study further supported the credibility of these findings above in previous researches.…”
Section: Discussionsupporting
confidence: 86%
“…They stimulate migration of both types, i.e., cutaneous and uveal melanoma [66][67][68][69]. Their role in chemoresistance of cancer cells to therapeutics is discussed [70]. Therefore, their targeting by small inhibitors was recently proposed in the literature [71].…”
Section: Discussionmentioning
confidence: 99%
“…Chemoresistance is widespread in HCC and characterizes tumor progression [49]. Interestingly, TTP overexpression in PLC/PRF/5 cells decreased the expression of the long transcript variant of the long-non coding RNA NEAT1 , NEAT1_v2 , which has been reported to enhance chemoresistance in different cancer cell lines, including hepatoma cells [50,51]. NEAT1 is one of the least stable long non-coding RNAs [52], a presumed tumor promoter, and associated with chemoresistance [50,53].…”
Section: Discussionmentioning
confidence: 99%